Species composition, distribution pattern and feeding ecology of demersal fish assemblages along coastal area off Pattani and Narathiwas provinces - ซุกรี, หะยีสาแม (มหาวิทยาลัยสงขลานครินทร์, 2011)
มหาวิทยาลัยสงขลานครินทร์